INFLUÊNCIA DE DIFERENTES FONTES DE COLOSTRO NA ONTOGENIA IMUNE E AMADURECIMENTO INTESTINAL DO LEITÃO - MACIAG, SHAIANA SALETE (2022)
Colostrum is essential for the development and survival of the swine neonate as it is the only way to acquire maternal immunity. The aim of this study was to compare the influence of colostrum from gilts, sows and dairy substitutes on immunological ontogenesis and intestinal maturation in piglets. For this, 60 piglets from 9 sows (OP> 5 and OP1) were divided into six groups: born from the sow or sow that remained with the mother throughout the period (SS/GG); born from the sow or sow that ingested colostrum from another sow/pill (GS/SG); born from the sow or sow that was fed with milk replacer (GMR/SMR). Piglets remained in the diet groups for 24 hours after birth, and were then returned to their respective mothers. Piglets were euthanized on days 1 and 28 of age to evaluate the concentrations of immunoglobulins and cytokines in the colostrum and serum of the piglets. Spleen, lymph node, thymus samples were collected to assess immune ontogenesis and small intestine to assess intestinal maturation. The concentration of immunoglobulins, Th1, Th2 and Th17 cytokines and the ability of B and T cells from lymphatic organs and blood mononuclear cells to respond to mitogens were higher in the groups that ingested colostrum from sows in the first 24 hours of life, being lower in the groups fed with milk replacer. There was no difference in the intestinal maturation of the groups. Therefore, we suggest a possible role of parity in colostrum composition, which contributes to exert a modulating action in the development of the immune response, and that the replacer negatively affects immune development and intestinal maturation, not being recommended as a colostrum substitute.